Ethylene Glycol Poisoning: An Unusual Cause of Altered Mental Status and the Lessons Learned from Management of the Disease in the Acute Setting - R. Singh; E. Arain; A. Buth; J. Kado; A. Soubani; N. Imran (Case Reports in Critical Care)
Ethylene glycol is found in many household products and is a common toxic ingestion. Acute ingestions present with altered sensorium and an osmolal gap. The true toxicity of ethylene glycol is mediated by its metabolites, which are responsible for the increased anion gap metabolic acidosis, renal tubular damage, and crystalluria seen later in ingestions. Early intervention is key; however, diagnosis is often delayed, especially in elderly patients presenting with altered mental status. There are several laboratory tests which can be exploited for the diagnosis, quantification of ingestion, and monitoring of treatment, including the lactate and osmolal gaps. As methods of direct measurement of ethylene glycol are often not readily available, it is important to have a high degree of suspicion based on these indirect laboratory findings. Mainstay of treatment is bicarbonate, fomepizole or ethanol, and, often, hemodialysis. A validated equation can be used to estimate necessary duration of hemodialysis, and even if direct measurements of ethylene glycol are not available, monitoring for the closure of the anion, lactate, and osmolal gaps can guide treatment. We present the case of an elderly male with altered mental status, acute kidney injury, elevated anion gap metabolic acidosis, and profound lactate and osmolal gaps.